Immune-Mediated Vascular Injury and Dysfunction in Transplant Arteriosclerosis - von Rossum, Anna; Laher, Ismail; Choy, Jonathan C. (Frontiers in Immunology, 2015)
Solid organ transplantation is the only treatment for end-stage organ failure but this life-saving procedure is limited by immune-mediated rejection of most grafts. Blood vessels within transplanted organs are targeted by the immune system and the resultant vascular damage is a main contributor to acute and chronic graft failure. The vasculature is a unique tissue with specific immunological properties. This review discusses the interactions of the immune system with blood vessels in transplanted organs and how these interactions lead to the development of transplant arteriosclerosis, a leading cause of heart transplant failure.